PEMBUATAN LKS ICT IPA TERPADU MENGINTEGRASIKAN KARAKTER MATERI STRUKTUR TUMBUHAN, SIFAT BAHAN, SISTEM GERAK, DAN PESAWAT SEDERHANA UNTUK SISWA KELAS VIII SMP - Sovia Marsilin; Asrizal Asrizal; Harman Amir (Universitas Negeri Padang, 2015)
Integrated sicence learning in junior high school is important. Beside that, formation of character values and use of ICT is also important in learning. One solution that can be done is to create an ICT worksheet of integrated science by integrating character values. The purpose of this research is to determine the validity, description, practicality, and effectiveness of ICT worksheet of integrated science by integrating character values. The type of research is Research and Development (R&D). Design of this research is before and after experiment. As object of research is ICT worksheet of integrated science by integrating character values. There are three instrument to collect data, those are validation sheet, practicality sheet, learning outcome test sheet, observation sheet of character values, performance sheet of student skills. Techniques of data analysis used are analysis of the validity, analysis of the practicality, and analysis of the effectiveness of product. Based on data analysis, there are two research results. First, ICT worksheet of integrated science by integrating character values is valid with average value is 88,70. ICT worksheet of integrated science by integrating character value has a home menu, introduction, content worksheets, evaluation, download, chatting, and discussion forum. Second, application of ICT worksheet of integrated science by integrating character values is practice that indicated by the average value from teachers and students respectively 87,32 and 84,74. Application of ICT worksheet of integrated science by integrating character values is also effective in science learning. That indicated by improvement of knowledge, character, and skill of students